Project “cyberasker” on the basis of the institute of social sciences and humanities of the knu named after. Zh. Balasagyn, as an educational platform for information support for the security of the younger generation of kyrgyzstanis (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article is a case study for the “CyberAsker” project based on the IGN KNU named after. Zh. Balasagyn, and partners: 1) Department of Political Science Research and Expertise, Institute of State and Law of the National Academy of Sciences of the Kyrgyz Republic. 2) And also, in the field of school education, the educational institution of the author’s physics and mathematics school-lyceum No. 61 Yakira E.B. Where we want to jointly implement a grant project to counteract the negative effect in the information space of the manifestation of extremism and terrorism among young people.
Keywords: information security, CyberAsker, youth, information technology, national security, prevention of extremism, school, college